Peran Mediasi Motivasi Kerja Pada Pengaruh Gaya Kepemimpinan, Lingkungan Kerja Dan Fasilitas Kerja Terhadap Kinerja Pegawai - Kristina Dewi Dayanti; Eko Prasojo (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2025)
This study aims to determine the effect of leadership style, work environment, and work facilities on employee performance with work motivation as a mediating variable on employees of the DIY Industry and Trade Service. This study used a saturated sampling technique with a total of 84 respondents. Data testing was carried out through validity, reliability, classical assumptions, multiple linear regression, t-test, coefficient of determination (R²) test, and Sobel test with the help of SPSS version 26. The results showed that leadership style had a positive and significant effect on employee performance, with a t-value of 2.336 and a significant value of 0.0022. The work environment had a positive but not significant effect on employee performance, with a t-value of 1.790 and a significant value of 0.077. Work facilities had a positive and significant effect on employee performance, with a t-value of 2.936 and a significant value of 0.004. Leadership style had a positive and significant effect on work motivation, with a t-value of 2.614 and a significant value of 0.011. The work environment has a positive and significant effect on work motivation, with a t-value of 2.886 and a significance of 0.005. Work facilities have a positive and significant effect on work motivation, with a t-value of 2.051 and a significance of 0.044. Work motivation has a positive and significant effect on employee performance, with a t-value of 0.774 and a significance of 0.441. The results of the Sobel test for the three mediation paths show values below 1.96, which indicates the absence of a significant mediation effect. so it can be concluded that performance improvement is more directly influenced by leadership style and work facilities than through work motivation.